PARA WIDYA VS APARA WIDYA DALAM VEDA - I Wayan Sindia Griya Danika (Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2019)
Science is the science that helps live a good life in helping everyday life and helps in spiritual life which will lead us to surrender to God. Science that helps in everyday life is the science that guides in carrying out life in the fields of mathematics, biology, chemistry and so on. Meanwhile, spiritual knowledge leads to return to one God. Science must be studied together, both general knowledge and spiritual knowledge, each of which is obtained collectively. It aids in living life and helps us see both in truth and in evil or darkness. In this study, using the literature study method by looking at the verses from the Vedic scriptures and trying to see the knowledge of the Widya and also Apara Widya in the Vedas used in everyday life. Then compare the virtues of giving priority to living life. The results of this study are to see how the roles of Widya and Apara Widya in life. And how Apara Widya and Para Widya provide a balance of knowledge for ourselves.